Employer Resistance to Union Certification: A Study of Eight Canadian Jurisdictions - Bentham, Karen (Relations industrielles / Industrial Relations, 2002)
SummaryThis study investigates the prevalence and impacts of employer resistance to union certification applications in eight Canadian jurisdictions. Employer resistance was found to be the norm, with 80 percent of employers overtly and actively opposing union certification applications. Analysis demonstrated that, depending on its form, employer opposition to union certification can impact upon both initial certification outcomes and on the probability the parties will establish and sustain a collective bargaining relationship. Furthermore, the study demonstrates that focusing only on the probability of certification success seriously underestimates the impact of employer opposition.